Iklan Komersial: Urgensi Nilai Syariah dalam Aplikasinya - Abdul Hakim (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2007)
Commercial advertising has been the main tool of many companies to sell their prducts. Unfortunately, the practice of contemporary advertising is contradictory to the initial objectives. Therefore, the use of islamic values in commercial advertising is recommended in securing responsible and healthy adversiting. Those favorable islamic values are the principles of honesty, simplicity, justice, cooperation, etiquette, legality, and benefit. This article is aimed to show the contribution of those islamic values in commercial advertising as well as to avoid negative impacts which often occur. By using the principle of islamic law, it will create the efficient and effective use of fund, promote the formation of helathy business competition and good comsumer’s behavior, reduction of anxiety among community caused by bad advertising, and the creation of dignified social harmony.